2010
DOI: 10.1016/j.febslet.2010.05.043
|View full text |Cite
|
Sign up to set email alerts
|

DEDD negatively regulates transforming growth factor‐β1 signaling by interacting with Smad3

Abstract: a b s t r a c tTransforming growth factor-b1 (TGF-b1) regulates a wide variety of cellular responses, such as proliferation, differentiation, migration and apoptosis. Here we report that death effector domain-containing DNA-binding protein (DEDD) physically interacts with Smad3. The inhibition of Smad3 by DEDD resulted in a reduction in TGF-b1/Smad3-mediated transcription. DEDD inhibited the functions of Smad3 by preventing Smad3 phosphorylation, which led to the reduced expression of TGF-b1/Smad3-targeted gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
(26 reference statements)
2
9
0
Order By: Relevance
“…Interestingly, a very recent study by Mori and colleagues report that DEDD deficiency results in a defect in uterine decidualization and infertile because of reducing Akt expression, indicating that DEDD is indispensable for the establishment of an adequate uterine environment to support early pregnancy in mice (43). This finding is consistent and support to the fact that DEDD is involved in the regulation of embryos developmental programs including EMT (19). However, it needs to point out, previous work indicated that DEDD can enter nucleus to inhibit rDNA transcription (25), regulate cell cycle, and inhibit cell mitosis to reduce cell and body size via modulation of rRNA synthesis (17), attenuate protein synthesis, and promote apoptosis (44,45).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Interestingly, a very recent study by Mori and colleagues report that DEDD deficiency results in a defect in uterine decidualization and infertile because of reducing Akt expression, indicating that DEDD is indispensable for the establishment of an adequate uterine environment to support early pregnancy in mice (43). This finding is consistent and support to the fact that DEDD is involved in the regulation of embryos developmental programs including EMT (19). However, it needs to point out, previous work indicated that DEDD can enter nucleus to inhibit rDNA transcription (25), regulate cell cycle, and inhibit cell mitosis to reduce cell and body size via modulation of rRNA synthesis (17), attenuate protein synthesis, and promote apoptosis (44,45).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, alterations in the expression of PI3KC3 result in either activation or inactivation of autophagy-dependent degradation of Snail/ Twist and other positive EMT markers. Despite we do not know the precise mechanism how DEDD interacts with PI3KC3 to maintain the stability of this protein and why loss of DEDD expression promotes the degradation of PI3KC3, recent work indicate that DEDD induces a diversity of cell biologic activity through interacting with several key molecules to attenuate or support the stability of these proteins in the cells (19,46). Thus, a key question to be addressed is: what program is responsible for shutdown or turn-on of DEDD expression under the physiologic or pathologic situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FOXM1 is also frequently aberrantly activated in many human cancers, including breast cancer (17,32). Specific and diverse TGF-β functions depend on the SMADs as a central node for the integration of TGF-β signaling with other signaling pathways (1,33). In the present study, we found that FOXM1 specifically interacts with SMAD3, which supports the recent observations that SMAD3, but not SMAD2, is required for TGF-β-induced metastasis in breast cancer (34).…”
Section: Tablesupporting
confidence: 80%